Short particle strengthened aluminium alloy, fracture toughness investigated with instrumented impact tests. (4th August 2014) - Varga, T.; Schabl, G.
For different aluminium matrix alloys values of fracture mechanics were determined and compared. The investigated materials were aluminium matrix alloys with an aluminium matrix of AA 6061 (AlMg 1 SiCu) reinforced by small alumina (Al2 O3 ) particles. Three point bend specimens with four different percentages of reinforcement, different notch orientation with electro eroded cuts or fatigue crack were investigated. The values of fracture mechanics were determined by instrumented impact with an impact velocity of 0.1 m/s. The outcome shows the behaviour of values of fracture mechanics over the percentage of reinforcement. The result shows that the instrumented impact test is a reasonable tool for the optimisation of materials for specific applications.